Double-coin foreign body in the oesophagus mimicking a button battery: a report of two cases with literature review - Sharma, Priyanka; Singh, Gautam B.; Saleem, Sadaf (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Ingestion of foreign bodies remains a common pediatric emergency, with coins being the most frequent culprit. However, the radio graphic appearance of stacked coins can closely resemble a button battery, a dangerous foreign body that requires emergent removal due to its potential for rapid esophageal injury. Authors report two pediatric patients who presented with suspected button battery ingestion but were intra-operatively found to have ingested two stacked coins. This article reviews their presentations, radio graphic findings, surgical management, and the critical importance of maintaining a high index of suspicion. A literature review highlights the challenges of radiologic differentiation and supports emergent esophagoscopy as the diagnostic and therapeutic gold standard.